Management Strategy of Idola Bumdes Agrourism Village to Realize Improving the Community's Economy of Sambibulu, Taman, Sidoarjo - Qoriani, Hersa Farida (Jurnal Informatika Ekonomi Bisnis, 2023)
The economy is part of human life, and a source in living life. The government in Indonesia has launched various rural development programs. Some people are starting to realize the importance of a change, by utilizing the plantation land into agro-tourism. One of the places where plantation land is used as an agro-tourism idol for Bumdes is in Sambi Bulu, Taman, Sidoarjo. The focus of the research is, How is the plantation management process becoming a Bumdes idol agritourism in Sambi Bulu, Taman, Sidoarjo?, What is the role of the Bumdes idol agro-tourism in realizing an increase in the community's economy in Sambi Bulu, Taman, Sidoarjo?, The research objectives were to describe the process of managing plantations to become idol Bumdes agritourism in Sambi Bulu, Taman, Sidoarjo to describe the role of agrotourism idol Bumdes agrotourism to realize economic improvement in the community in Sambi Bulu, Taman, Sidoarjo. The research methodology is a qualitative approach and this type of research is descriptive qualitative. Data collection techniques using unstructured interviews, passive participatory observation and documentation. Data analysis using data reduction, data presentation and conclusions. The validity of the data in this study uses source triangulation. The results of this study are: the management process carried out is to make changes, make fishing ponds, planted commodities, care for plants (fertilizing irrigation and others), maintenance of fish ponds, making game rides. and planting suitable plants, as a place of study and tourism based on artificial open agriculture, The role of idol-owned agro-tourism in improving the rural economy is to provide job opportunities, communities around agro-tourism are given the freedom to sell in agro-tourism, provide counseling, transmit knowledge through various training -training. However, the existence of agro-tourism cannot increase the income of workers and the surrounding community.